Backflow to Rural Social Identity: The Case of Ecotourism Potency to Protect Sangrawayang Villagers Asset in Indonesia - Ahmad Izudin (JURNAL ILMIAH SYI'AR, 2021)
This paper describes the social identity and rural ecotourism potency of asset-based Sangrawayang village in Indonesia through a case study approach. It explores how the rural development policy becomes a means of social transformation influences villagers in the context of the emerging local elites and increasing livelihood in their home villages. While available ecotourism potency, based on natural and cultural assets, protects villagers in enacting village laws and providing welfare programs independently, they limit the means and scope of ecotourism potency to powerful their living resilience. This study suggests that the potential of rural ecotourism should be encouraged through policy changes. Villagers have not recognized their assets and potential caused by social stratification, land ownership, and power inequality, so initiatives to powerful social identity tend to be neglected.